Internal Jugular and Subclavian Vein Thrombosis in a Case of Ovarian Cancer - Hiroto Moriwaki; Nana Hayama; Shouko Morozumi; Mika Nakano; Akari Nakayama; Yoshiomi Takahata; Yuusuke Sakaguchi; Natsuki Inoue; Toshiki Kubota; Akiko Takenoya; Yoshiko Ishii; Haruka Okubo; et al. (Case Reports in Otolaryngology)
Central venous catheter insertion and cancer represent some of the important predisposing factors for deep venous thrombosis (DVT). DVT usually develops in the lower extremities, and venous thrombosis of the upper extremities is uncommon. Early diagnosis and treatment of deep venous thrombosis are of importance, because it is a precursor of complications such as pulmonary embolism and postthrombotic syndrome. A 47-year-old woman visited our department with painful swelling on the left side of her neck. Initial examination revealed swelling of the region extending from the left neck to the shoulder without any redness of the overlying skin. Laboratory tests showed a white blood cell count of 5,800/mm3 and an elevated serum C-reactive protein of 4.51 mg/dL. Computed tomography (CT) of the neck revealed a vascular filling defect in the left internal jugular vein to left subclavian vein region, with the venous lumina completely occluded with dense soft tissue. On the basis of the findings, we made the diagnosis of thrombosis of the left internal jugular and left subclavian veins. The patient was begun on treatment with oral rivaroxaban, but the left shoulder pain worsened. She was then admitted to the hospital and treated by balloon thrombectomy and thrombolytic therapy, which led to improvement of the left subclavian venous occlusion. Histopathologic examination of the removed thrombus revealed adenocarcinoma cells, indicating hematogenous dissemination of malignant cells.